Structure and Macular Sensitivity Characteristic After Silicone Oil Removal in Primary Rhegmatogenous Retinal Detachment - Haryono, Aditia Apriyanto; Widyanatha, Made Indra; Iskandar, Erwin; Kartasasmita, Arief Sjamsulaksan; Virgana, Rova; Ihsan, Grimaldi (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2022)
Introduction: Silicone oil (SO) is an endotamponade to manage several retinal detachments.The emulsification of silicone oil is one of the complications that may occur in several patients. Retinal macular changes may occur even with successful tamponade. Purpose: to describethe structure and macular sensitivity characteristic after silicone oil removal in primary rhegmatogenous retinal detachment (RRD). Methods: a prospective, descriptive case series study of who underwent SO tamponade for primary RRD. Optical coherence tomography (OCT) and microperimetry (MP-3) were conducted before SO removal and one week after SO removal. Result: There were nine eyes that met the criteria. The mean age of the patients was 53.3±14 years. Most of the patients use silicon 1300 (66.67%) and under six months (77.8%) duration of silicone tamponade. After silicone oil removal, mean macular sensitivity in the central fovea decreased from 12.44 dB to 12.11 dB, and parafovea increased from 18.33 dB to 19.00 dB.The mean macular thickness in the fovea decreased from 269.89μm to 260μm. The mean macular thickness in parafovea was an increase from 316.16 to 328.00μm Conclusion: There was an increase in macular sensitivity and thickness at parafovea after one- week silicone oil removal in primary rhegmatogenous retinal detachment.